Diferenciação oxidativa em dispositivos temporários de ancoragem de titânio e aço - Picolo, Thiago Oszika (2020)
Corrosion of orthodontic mini-implants or temporary anchoring devices (TADs) has been proposed as a contributing factor to inflammation of oral tissues, which in turn contributes to the clinical success of mini-implants (KNUTSON, 2013). Thus, it is necessary to use a material that presents greater resistance than Titanium and its alloys (SQUEFF et al., 2008; CHANG et al., 2015). Currently, stainless steel TADs for orthodontic anchorage procedures have a high success rate, which has led to a high demand for professionals in the area (CHANG et al., 2015). This study tested the hypothesis that temporary anchoring devices (TADs) made of 316L steel are more resistant to corrosion even in the fluorine environment, than DATs manufactured in addition to titanium alloys, for both potentiostat electrochemical meters. Materials and Methods: Four pieces of each material were tested in each test set, an application of Fusayama artificial saliva was used as an electrolytic solution in this study of corrosion in vitro, without flowing in its composition and in the second moment with 1500ppM of fluorine in its composition. In the test, a cathodic polarization was performed after the activation of this voltage for 5 minutes or until the corrosion pins were obtained. In artificial saliva, containing up to 1500ppmF- for each material and, this test was repeated with new samples of each material in artificial saliva solution without fluoride. Results: The results of the induction current scale were entered without OriginPro8 software for making value graphs. All metal alloys currently used in the Ti6Al4V alloy showed good resistance to corrosion in artificial saliva. However, the corrosion of these alloys occurs in contact with high temperatures, unlike 316L steel alloy, which in addition to corrosion makes the surface passivated.